Quality evaluation of simvastatin compounded capsules - Flávia Dias Marques-Marinho; José Carlos da Costa Zanon; Emilia Sakurai; Ilka Afonso Reis; Angélica Alves Lima; Cristina Duarte Vianna-Soares (Universidade de São Paulo, 2011)
Simvastatin is commercially available as tablets and compounded capsules in Brazil. Very few reports regarding these capsules' quality, and consequently their efficacy, are available. The pharmaceutical quality of 30 batches of 20 mg simvastatin capsules from the market was evaluated by weight determination, content uniformity, disintegration (Brazilian Pharmacopeia), assay and dissolution test (USP32 tablet monograph). A HPLC method was developed for assay, content uniformity and dissolution test, and specifications were also established. Out of the 30 batches evaluated, 29 showed capsule disintegration within 45 min and individual weight variation was within ±10% or ±7.5% relative to average weight, for < or > 300 mg, respectively. Only 27 batches met dissolution test criteria with values >80% of the labeled amount in 45 min; 21 batches showed simvastatin content between 90.0-110.0% of the labeled amount and 19 batches had at least 9 out of 10 capsules with content uniformity values between 85.0-115.0% of the labeled amount with RSD<6.0%. Only 14 of all (30) batches fully met pharmacopeial quality standards. The establishment of test conditions and specification parameters for simvastatin capsules showed that there are relevant pharmacopeial quality differences between batches compounded by different pharmacies. For 53.33% of the tested products hypercholesterolemic treatment efficacy may be compromised. No Brasil, a sinvastatina está comercialmente disponível na forma de comprimidos e cápsulas manipuladas. Poucos relatos estão disponíveis sobre a qualidade e, consequentemente, a eficácia dessas cápsulas. A qualidade de 30 lotes de sinvastatina 20 mg cápsulas do mercado foi avaliada através da determinação de peso, uniformidade de conteúdo, desintegração (Farmacopéia Brasileira), doseamento e teste de dissolução (monografia comprimidos USP32). Método por CLAE foi desenvolvido para o doseamento, uniformidade de conteúdo e teste de dissolução; além disso, especificações foram estabelecidas. Dos 30 lotes avaliados, 29 apresentaram desintegração da cápsula até 45 min e a variação do peso individual foi ± 10% ou ± 7,5% em relação ao peso médio, se < ou > 300 mg, respectivamente. Apenas 27 lotes preencheram os critérios do teste de dissolução com valores > 80% da quantidade rotulada, em 45 min, 21 lotes apresentaram conteúdo de sinvastatina entre 90,0-110,0% do valor rotulado e 19 lotes apresentaram pelo menos 9 em 10 cápsulas, com valores de uniformidade de conteúdo entre 85,0 -115,0% da quantidade rotulada com RSD < 6,0%. Apenas 14 de todos os lotes (30) atenderam completamente os padrões de qualidade farmacopéicos. O estabelecimento das condições para os testes e de especificações para os parâmetros das cápsulas de sinvastatina mostrou que houve diferenças relevantes na qualidade farmacopeica entre os lotes das cápsulas manipuladas por distintas farmácias. A eficácia do tratamento hipercolesterolêmico poderia estar comprometida para 53,33% dos produtos testados.